Differential activity of transcription factor Sox9 in early and adult oligodendroglial progenitor cells - Hassel, Lisa; Fröb, Franziska; Küspert, Melanie; Hillgärtner, Simone; Arnold, Philipp; Huang, Wenhui; Kirchhoff, Frank; Wegner, Michael (Glia, 2023)
The high-mobility-group domain-containing transcription factor Sox9 confers glial competence to neuroepithelial precursors in the developing central nervous system and is an important determinant of astroglial and oligodendroglial specification. In oligodendroglial cells, it remains expressed in oligodendrocyte progenitor cells (OPCs) of the developing nervous system, but is shut off in differentiating oligodendrocytes as well as in OPCs that persist in the adult nervous system. To better understand the role of Sox9 in OPCs, we generated mouse models that allowed oligodendroglial expression of a Sox9 transgene during development or in the adult. With transgene expression beginning in the last trimester of pregnancy, the number of OPCs increased dramatically, followed by comparable gains in the number of pre-myelinating and myelinating oligodendrocytes as assessed by marker gene expression. This argues that Sox9 boosts oligodendrogenesis during ontogenetic development at all stages, including terminal oligodendrocyte differentiation. When Sox9 transgene expression started in the adult, many transgene-expressing OPCs failed to maintain their progenitor cell identity and instead converted into myelinating oligodendrocytes. As infrequent and inefficient differentiation of adult OPCs is one of the main obstacles to effective remyelination in demyelinating diseases such as Multiple Sclerosis, increased Sox9 levels in adult OPCs may substantially increase their remyelination capacity.
CRIS-Team Scopus Importer:2023-04-21
Keywords: glia; HMG; myelin; oligodendrocyte; Sox; Sry